The assessment of graduate sustainability attributes in the workplace: Potential advantages of using the theory of planned behaviour (TPB). (20th November 2019) - Holdsworth, Sarah; Sandri, Orana; Thomas, Ian; Wong, Peter; Chester, Andrea; McLaughlin, Patricia
Abstract: Sustainability in higher education aims to educate learners, as both citizens and future professionals, to build capacity to bring about a more sustainable future. As such, sustainability education can be seen as part of enabling work-ready graduates. Many universities, globally, have begun to embed sustainability capabilities into their degree programs. However, there is a gap in existing methods for assessing graduate application of the associated learning outcomes, post degree-completion. The Theory of Planned Behaviour (TPB) has been suggested and applied in the development of an assessment tool to address this limitation. The TPB considers human behaviour is influenced by a number of factors, the measurement of which allows one to understand the likelihood of a person executing a particular behaviour. This paper presents an overview and explanation of how TPB could be applied to graduate sustainability capability assessment, thereby, offering insight into how graduate learning is applied in professional settings. Highlights: TPB is a valid theoretical foundation to assess graduate sustainability attributes. Graduate attribute assessment beyond self-assessment is achieved. Insight into the professional application of sustainability graduate learning. TPB has the potential to provide graduate data to inform curriculum renewal.